Effect of Storage Conditions and Storage Periods on Seed Germination of Kesambi (Schleichera oleosa(Lour.) Merr) - Febrina Artauli Siahaan (Jurnal Perbenihan Tanaman Hutan, 2017)
The availability of kesambi seed for planting is not always sufficient, so the proper seed storage to ensure the availability and maintenance the seed quality need to know. The purpose of this research was to determine the effect of different storage periods and storage conditions towards seed germination of kesambi. This experimental design used completely randomized design, consists of with 2 factors, storage conditions (room temperature, sealed jar consist of silica gel and low temperature) and storage periods (30, 60, 90 days) with 3 replications for each treatment. The results showed that the germination percentage, germination rate, the initiation of germination and shoots emergence were affected by the storage conditions, while storage periods and the interaction of the factors only affected the germination rate. The highest germination (55 %) found in seeds stored in sealed jars contain of silica gel for 30 days, with a germination rate of 7 days and the initiation of germination and shoots emergence of 12 days and 17 days, while the lowest value were found in seeds which stored at low temperatures.